FINANCIAL TECHNOLOGY INVESTMENTS AND THEIR IMPACT ON ECONOMIC GROWTH - Yassine MIMOUNI; Mouna BESSOUYAH (Modern Management Review)
This study aims to measure the impact of financial technology investments on economic growth around the world during the period (2014-2023). The error correction model ECM was used, and the results of the estimates showed that there is no causal relationship between the two variables in the short term; and after testing After valuation of transactions, it turned out that the error correction coefficient CointEq is negative and significant; this explains the existence of a long-term equilibrium relationship between the study variables, and from the test of the analysis of the statement, The shocks that reflect any change in the level of GDP variable by explaining the variance that the occurrence of any single structural shock in financial technology investments by 1% has a positive impact on GDP,  and after analyzing the response functions to random shocks, it was found that the degree of response of both variables has been achieved since the first period.